2014
DOI: 10.3389/fonc.2014.00207
|View full text |Cite
|
Sign up to set email alerts
|

miR-21 Expression in Cancer Cells may Not Predict Resistance to Adjuvant Trastuzumab in Primary Breast Cancer

Abstract: Trastuzumab is established as standard care for patients with HER2-positive breast cancer both in the adjuvant and metastatic setting. However, 50% of the patients do not respond to the trastuzumab therapy, and therefore new predictive biomarkers are highly warranted. MicroRNAs (miRs) constitute a new group of biomarkers and their cellular expression can be determined in tumor samples by in situ hybridization (ISH) analysis. miR-21 is highly prevalent and up-regulated in breast cancer and has been linked to dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 55 publications
0
15
0
Order By: Relevance
“…Finally, to study if the mechanisms identified in these cell line experiments are also present in breast tumours we used samples included in the population-based breast cancer project SCAN-B 23 . This analysis may be complicated by the fact that miR-21-5p has a dynamic expression in different cell types within the tumour 24 while the tumour data represents bulk tumour RNA with varying percentages of cancer cells. We selected 186 breast tumour samples, produced small RNA sequencing data from the extracted total RNA and used poly(A)-positive mRNA-sequencing data to classify samples into the intrinsic subtypes according to the expression of genes included in the PAM50 classifier.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, to study if the mechanisms identified in these cell line experiments are also present in breast tumours we used samples included in the population-based breast cancer project SCAN-B 23 . This analysis may be complicated by the fact that miR-21-5p has a dynamic expression in different cell types within the tumour 24 while the tumour data represents bulk tumour RNA with varying percentages of cancer cells. We selected 186 breast tumour samples, produced small RNA sequencing data from the extracted total RNA and used poly(A)-positive mRNA-sequencing data to classify samples into the intrinsic subtypes according to the expression of genes included in the PAM50 classifier.…”
Section: Resultsmentioning
confidence: 99%
“…MiR-15a is a member of the pro-apoptotic miRNA cluster and several studies have confirmed the decreased expression in breast cancer [41,42]. MiR-21 is an oncogene which is over-expressed and plays as an anti-apoptotic factor in most breast cancers [20,41,43]. MiR-200c and miR-141 are two members of the miR-200 family, which have been shown to function as tumour-suppressive miRNAs by targeting multiple oncogenic factors.…”
Section: Effect Of Silibinin On Expression Mirnamentioning
confidence: 99%
“…Multiplex analysis of different miRNAs enables distinguishing between different types of cancers [ 22 , 103 ]. Examples of specific miRNAs that show high changes in cancerous cells that were imaged with ISH methods are miR-21 in colon adenocarcinomas and gliomas as well as pancreatic and breast cancer [ 99 , 100 , 104 , 105 , 106 , 107 ], miR-10b in pancreatic ductal adenocarcinoma [ 108 ] and miR-221 in breast cancer [ 109 ].…”
Section: Applications Of Small Rna Ishmentioning
confidence: 99%